OPTIMIZING HALAL MSME FINANCING THROUGH ARTIFICIAL INTELLIGENCE-BASED SHARIA FINTECH TO INCREASE ECONOMIC INDEPENDENCE - Efendi, Erizal Candra; Juniyanti Hsb, Hafni (Program Studi Manajemen Keuangan Syariah, 2026)
This study aims to explore the optimization of halal MSME financing through Sharia-based fintech utilizing Artificial Intelligence (AI) to enhance economic independence. The research employs a qualitative library research method, analyzing literature from academic journals, government reports, and fintech publications related to Sharia-compliant financial technologies. The results indicate that Sharia fintech provides inclusive, ethical, and flexible financing for halal MSMEs through profit-sharing contracts like mudharabah and musyarakah. The integration of AI enhances operational efficiency, risk assessment, and compliance with Sharia principles. Challenges include regulatory gaps, low digital literacy among MSMEs, and ethical concerns regarding AI algorithms. Strategies such as regulatory adaptation, education programs, ethical governance frameworks, and multi-sector collaboration are essential to maximize the benefits of Sharia fintech for MSMEs, strengthening the halal economy and promoting sustainable economic independence.